Factors Associated With Severe Fever With Thrombocytopenia Syndrome in Endemic Areas of China - Jiang, Xiaolin; Wang, Yiguan; Zhang, Xiaomei; Pang, Bo; Yao, Mingxiao; Tian, Xueying; Sang, Shaowei (Frontiers in Public Health, 2022)
Objective To explore the influence of climatic, environmental and socioeconomic factors on SFTS occurrence in Shandong Province, China. Methods We used generalized additive model to estimate the association between SFTS cases and climatic factors, environmental factors and socioeconomic factors, including annual average temperature, precipitation, land cover, normalized difference vegetation index, altitude, population density, meat production, milk production, and gross domestic product (GDP). Results There were a total of 4,830 cases reported in 100 (70.9%) counties and districts in Shandong Province from 2010 to 2020. The results showed that the annual average temperature, precipitation, forest and grassland coverage rate, altitude and meat production (square root transform) had a reversed “V” relationship with SFTS occurrence, with the inflection points around 12.5–13.0°C in temperature, around 650 mm in precipitation, around 0.3 in forest and grassland coverage rate, around 300 m in altitude, and around 200–300 tons in meat production (square root transform), respectively. SFTS occurrence had a “V” relationship with milk production (square root transform) and GDP (square root transform), with the inflection points around 100–200 tons in milk production (square root transform), and around 150,000–200,000 yuan in GDP (square root transform), respectively. Conclusions Climatic, environmental, and socioeconomic factors contributed to the heterogeneous distribution of SFTS in Shandong Province, and the influence of these factors on SFTS occurrence was nonlinear.